Improper textual borrowing practices: Evidence from Iranian applied linguistics journal articles. Issue 35 (September 2018) - Jalilifar, Alireza; Soltani, Parvin; Shooshtari, Zohreh G.
Abstract: The current study investigated inappropriate textual borrowings, in Iranian English scholarly journals of applied linguistics. They were examined in terms of their frequency and patterns as well as the way they function in rhetorical organization of the texts. The originality check was performed on the Introduction sections of 115 journal articles, using the text matching software (iThenticate) along with human inspection to exclude irrelevant or coincidental matches. The findings indicate that nearly one third of the corpus contained more than 20 percent matched words. Analyzing the matched sources revealed four patterns of source misuse among which the use of secondary citations was the most frequently occurring pattern. The instances of illegitimate borrowing were also analyzed in relation to the macro-structural configuration of the introduction in light of Swales' (1990, 2004) CARS model. The bulk of plagiarized content was traced to the opening move (Establishing a territory) reflecting the academic authors' challenge in setting up a unique context for their research study. The findings have implications for scholarly writers and journal publishers as well as EAP teachers and students to develop a deeper understanding of textual borrowing practices and the necessity to incorporate education into prevention and regulation.